FACTORS AFFECTING SALESPERSON PERFORMANCE IN SMEs CREATIVE INDUSTRY OF CENTRAL JAVA - Asyhari, Asyhari; Yuwalliatin, Sitty (Jurnal Aplikasi Manajemen, 2020)
This study aims to examine the influence of emotional intelligence, spiritual intelligence, personality and competency toward salesperson performance in SMEs Creative Industry of Central Java. The research uses survey design which a quantitative approach. Data collected from 150 respondents by distributing questionnaires, and then Structural Equation Modeling (SEM) is used to test the hypotheses. The finding of this study demonstrated that emotional intelligence, spiritual intelligence, personality and competency have a positive influence on salesperson performance. The originality of this study is the important role of the internal salesperson in order to enrich the sales management literature. This research has limitations related to indicators are used; therefore future researchers are suggested to expand the indicators of measure salesperson performance and other variables.